Detection of pesticide residues on fruit surfaces using laser induced breakdown spectroscopy. Issue 97 (21st October 2015) - Du, Xiaofan; Dong, Daming; Zhao, Xiande; Jiao, Leizi; Han, Pengcheng; Lang, Yun
<x xml:space="preserve">Abstract</x> The detection of chlorpyrifos residue on the surface of apples by laser induced breakdown spectroscopy (LIBS) was explored, establishing a new method for the fast detection of pesticide residues on fruit.